Introduction to IDTC Special Issue: Joule's Bicentenary History of Science, Foundations and Nature of Science - Pisano, Raffaele (2020)
James Prescott Joule’s (1818–1889) bicentenary took place in 2018 and commemorated by the IDTC with a Symposium—‘James Joule’s Bicentenary: Scientific and Pedagogical Issues Concerning Energy Conservation’—at the European Society for the History of Science (ESHS & BSHS), 14th–17th September, 2018, in London. This symposium had three main objectives: It aimed specifically to celebrate James Joule’s achievements considering the most recent historiographical works with a particular focus on the principle of conservation of energy; It served the purpose of discussing the scientific and pedagogical issues related to heat, energy and work and how they are presented in textbooks and worked out in classrooms; It also provided discussions on the present situation of teaching and learning science through the use of History of Science, both in K-12 and college level with an emphasis on energy and related concepts. In the following, the Introduction of this Special Issue on Joule is presented.